Prevention of LPS-Induced Acute Lung Injury in Mice by Progranulin - Zhongliang Guo; Qinchuan Li; Yang Han; Yongjie Liang; Zengguang Xu; Tao Ren (Hindawi Limited, 2012)
The acute respiratory distress syndrome (ARDS), a clinical complication of severe acute lung injury (ALI) in humans, is a leading cause of morbidity and mortality in critically ill patients. Despite decades of research, few therapeutic strategies for clinical ARDS have emerged. Here we carefully evaluated the effect of progranulin (PGRN) in treatment of ARDS using the murine model of lipopolysaccharide (LPS)-induced ALI. We reported that administration of PGRN maintained the body weight and survival of ALI mice. We revealed that administration of PGRN significantly reduced LPS-induced pulmonary inflammation, as reflected by reductions in total cell and neutrophil counts, proinflammatory cytokines, as well as chemokines in bronchoalveolar lavage (BAL) fluid. Furthermore, administration of PGRN resulted in remarkable reversal of LPS-induced increases in lung permeability as assessed by reductions in total protein, albumin, and IgM in BAL fluid. Consistently, we revealed a significant reduction of histopathology changes of lung in mice received PGRN treatment. Finally, we showed that PGRN/TNFR2 interaction was crucial for the protective effect of PGRN on the LPS-induced ALI. Our findings strongly demonstrated that PGRN could effectively ameliorate the LPS-induced ALI in mice, suggesting a potential application for PGRN-based therapy to treat clinical ARDS.